Attitude of Romanian Consumers Related to Products' Ecological Labelling - Vasile Dinu; Ion Schileru; Anca Atanase (Amfiteatru Economic Journal, 2012)
The consumers play an important role in the protection of environment by their choices when they purchase products. Consequently, with a view to manufacture products with minimum impact on environment as well as to influence the conduct of consumers and improve the ecological performance of products and services, the ISO 14000 standards were elaborated for ecological labelling and analysis of life cycle of products and national and regional systems of ecological labelling of products were introduced. Also, in order to support a healthy and non-polluting environment, the European Commission adopted, pursuant to some specialised studies, a legislation related to the assignment of the condition of ecological product to different categories of products and services, having as purpose the environment protection and ensuring a durable consumption. At the same time, in order to improve the range of instruments of environment protection, financial and technical instruments were introduced as well The European Eco-Management and Audit Scheme – EMAS, but also the European ecological label Eco-label. The European ecological label is useful in order to supply to the consumers essential information that may allow them to make choices knowingly, acting as well as a passport that authorises the free circulation of products on the European territory. All the European Union's states adopted the communitarian ecological label. Consequently, the integration of Romanian in the European Union imposed a range of measures related to the procedure of granting the ecological label. In Romania, there is a specific legislative frame concerning the determination of the procedure of granting the ecological label and of their conditions of use. Each group of products to which a label is assigned is governed by a specific legislation that sets forth the granting criteria. The main objectives of article concern the featuring of some fundamental elements related to eco-labelling by emphasizing the main theoretical-methodological and conceptual delimitations, the presentation of this phenomenon on international, European and national level, ending in an analysis related to the attitude of Romanian consumers towards the ecological labelling of products.
Keywords: D18; F18; Q56; 330; eco-labelling; the European ecological label; eco-labelling in Romania; consumers